Religious Experience Of Sapta Darma Followers In The Temple Centre Sapta Rengga Yogyakarta City - Iwan Wahyudi; Miftahurrahmah; Susanti Melinda; Ihlasul Amal; Kholidun Najib; Hilmi Intan; Bunga Yunita; Lahiria Wuliana Ahromi (ASTEEC, 2024)
This research aims to understand the religious experiences of Sapta Darma adherents through the theoretical perspective of Joachim Wach. Sapta Darma believers are a group of believers who have spiritual views and practices that are 'unique' in Indonesia. In this study, researchers used Joachim Wach's theoretical framework, religious experiences were analyzed through three main components: experience dimensions, expression dimensions, and consequence dimensions. This research uses a qualitative method with a phenomenological approach to explore the religious experiences of Sapta Darma adherents. Data was collected through in-depth interviews with believers and participant observation of their religious rituals and practices. The results of the research show that the religious experience of Sapta Darma Sanggar Sanggar Candi Sapta Rengga, Yogyakarta City includes religious experiences which are often experienced through prostration, digging and special rituals. The expression dimension is seen in the form of prayers, mantras and symbols used in religious practices. Meanwhile, the consequence dimension includes changes in behavior and outlook on life of Sapta Darma adherents. Analysis based on Joachim Wach's theory reveals that the religious experiences of Sapta Darma adherents not only provide meaning and purpose in their lives but also form a strong spiritual identity. This study provides insight into how religious experiences can be articulated and internalized in local cultural contexts.